2016
DOI: 10.1038/modpathol.2015.128
|View full text |Cite
|
Sign up to set email alerts
|

Lobular neoplasia detected in MRI-guided core biopsy carries a high risk for upgrade: a study of 63 cases from four different institutions

Abstract: There are certain criteria to recommend surgical excision for lobular neoplasia diagnosed in mammographically detected core biopsy. The aims of this study are to explore the rate of upgrade of lobular neoplasia detected in magnetic resonance imaging (MRI)-guided biopsy and to investigate the clinicopathological and radiological features that could predict upgrade. We reviewed 1655 MRI-guided core biopsies yielding 63 (4%) cases of lobular neoplasia. Key clinical features were recorded. MRI findings including m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 32 publications
1
8
0
Order By: Relevance
“…There is a paucity of data, however, as to the rate of upgrade and need for excision of ADH and lobular neoplasia when the diagnosis is made following abnormal MRI. Studies have shown that high‐risk lesions detected via MRI, will be upgraded to malignancy upon excision, at a variable rate, ranging from 15%‐50% for ADH and 0%‐33% for lobular neoplasia (LN) …”
Section: Introductionsupporting
confidence: 85%
See 3 more Smart Citations
“…There is a paucity of data, however, as to the rate of upgrade and need for excision of ADH and lobular neoplasia when the diagnosis is made following abnormal MRI. Studies have shown that high‐risk lesions detected via MRI, will be upgraded to malignancy upon excision, at a variable rate, ranging from 15%‐50% for ADH and 0%‐33% for lobular neoplasia (LN) …”
Section: Introductionsupporting
confidence: 85%
“…Review of the literature provides minimal consensus regarding the risk of upgrade for MRI‐detected atypical lesions, with estimates ranging from 15%‐50% for ADH and 0%‐33% for LN . The overall upgrade rate of 24.3%, observed in the present study, is consistent with cited literature for MRI‐detected lesions, as well as for mammographically identified atypical lesions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, in certain instances these lesions represent a dominant finding, as in lobular carcinoma in situ. 26,27 Normal breast tissue can show significant enhancement depending on the phase of the menstrual cycle, further complicating image interpretation. 1,24 Twenty-one of our biopsies showed normal breast tissue, of which 11 patients had follow-up imaging studies documenting resolution of the initial lesion, 4 patients had repeat biopsies showing either benign breast tissue or fibrocystic changes, and 1 patient underwent total mastectomy with concordant results.…”
Section: Discussionmentioning
confidence: 99%